Precipitated phase reinforced hexagonal boron nitride composite ceramic material and preparation method thereof
By introducing a composite phase into hexagonal boron nitride ceramics and using rapid hot pressing sintering and heat treatment technology, precipitation-reinforced hexagonal boron nitride composite ceramic materials were prepared, which solved the problem of low hardness and strength of traditional hexagonal boron nitride ceramic materials and achieved higher density and mechanical properties.
Patent Information
- Application Number
- CN202510917382.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-03
- Publication Date
- 2025-09-16
AI Technical Summary
Traditional hexagonal boron nitride ceramic materials are difficult to sinter to a dense consistency at high temperatures, resulting in low hardness and strength, making it difficult to meet the performance requirements of harsh working conditions.
By introducing composite phases such as magnesium oxide, aluminum oxide and magnesium aluminum spinel, combined with rapid hot pressing sintering and heat treatment technology, precipitation phase-reinforced hexagonal boron nitride composite ceramic materials were prepared.
The density and mechanical properties of hexagonal boron nitride ceramics are significantly improved, and their application performance under harsh working conditions is enhanced.
Smart Images

Figure CN120647391A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of material science and engineering technology, and relates to a precipitation phase reinforced hexagonal boron nitride composite ceramic material and a preparation method thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance understanding of the overall background of the invention and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to those skilled in the art.
[0003] Hexagonal boron nitride (h-BN) has a unique crystal structure, excellent thermal shock resistance and is easy to process. It can be used in various fields such as horizontal continuous casting separation rings, metal melting crucibles, amorphous nozzles and high-temperature metal electrolytic cells.
[0004] However, hexagonal boron nitride is difficult to sinter to a high density at high temperatures. Currently, the hot-pressed hexagonal boron nitride ceramic materials prepared by domestic and foreign companies generally require temperatures above 1800°C and sintering pressures above 25 MPa to achieve relatively high density.
[0005] Therefore, it is urgent to solve the problem that traditional hexagonal boron nitride ceramic materials have low hardness and strength, which makes it difficult to meet the performance requirements of harsh working conditions. Summary of the Invention
[0006] In order to solve the above problems, the present invention provides a precipitation phase strengthened hexagonal boron nitride composite ceramic material and a preparation method thereof.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions: The first aspect of the present invention provides a precipitation phase strengthened hexagonal boron nitride composite ceramic material, the raw materials including: hexagonal boron nitride powder and a composite phase, the composite phase is composed of the following raw materials in parts by weight: 0.01 to 52 wt% of magnesium oxide, 0 to 68 wt% of aluminum oxide, and 0 to 70 wt% of magnesium aluminum spinel.
[0008] A second aspect of the present invention provides a method for preparing a precipitate-reinforced hexagonal boron nitride composite ceramic material, comprising: mixing hexagonal boron nitride, magnesium oxide, aluminum oxide, and magnesium aluminum spinel to obtain a first product; Ball milling the first product and drying it to obtain a second product; The second product is sintered under vacuum conditions to obtain a third product: The third product is obtained by heat-treating the product under an inert atmosphere.
[0009] The present invention ensures the density of the boron nitride ceramic by sintering, and at the same time, cooperates with heat treatment to control the precipitation phase, thereby further improving the performance of the boron nitride ceramic.
[0010] Beneficial effects of the present invention (1) The present invention prepares a hexagonal boron nitride composite ceramic material with a reinforcement phase precipitated inside the composite phase and at the phase boundary between the composite phase and the hexagonal boron nitride matrix phase through innovative design of raw materials and preparation methods; and can also obtain reinforcement phases with different contents and morphologies at the phase boundary of the material and in the composite phase by different sintering temperatures and heat treatment times; and improves the comprehensive performance of the product by improving interface bonding and strengthening the precipitation phase; thereby effectively solving the technical defect in the prior art that the traditional hexagonal boron nitride ceramic material has low hardness and strength, which makes it difficult to meet the performance requirements of harsh working conditions.
[0011] (2) The preparation method of the present invention is simple, practical, and easy to promote. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] The accompanying drawings, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute improper limitations on the present invention.
[0013] Figure 1 In the technical solutions provided in the embodiments of the present application, the XRD patterns of the Al-1750-0 sample, the Al-1750-1 sample, the Al-1750-3 sample, and the Al-1750-5 sample; Figure 2 In the technical solution provided in the embodiment of this application, the SEM morphology of the Mg-1650-1 sample and the Mg-1650-5 sample; Figure 3 A schematic flow chart of a method for preparing a precipitation phase-reinforced hexagonal boron nitride composite ceramic material in the technical solution provided in an embodiment of the present application. DETAILED DESCRIPTION
[0014] It should be noted that the following detailed descriptions are exemplary and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0015] Unless otherwise defined, all professional and scientific terms used herein have the same meaning as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. Unless otherwise specified, the reagents or raw materials used in the present invention are used in accordance with conventional methods in the art or according to product specifications. Similarly, unless otherwise specified, the test methods of the present invention are also tested in accordance with conventional methods in the art or the common methods or standards in the industry. In addition, any methods and materials similar to or equivalent to the described contents can be applied to the inventive method. The preferred embodiments and materials described herein are for demonstration purposes only.
[0016] The present invention provides a precipitation phase reinforced hexagonal boron nitride composite ceramic material. The raw materials include: hexagonal boron nitride powder and a composite phase. The composite phase is composed of the following raw materials in parts by weight: 0.01-52wt% of magnesium oxide, 0-68wt% of aluminum oxide, and 0-70wt% of magnesium aluminum spinel.
[0017] In some embodiments, the mass of the composite phase is 10-50 wt % of the total mass of the ceramic material.
[0018] Magnesium-aluminum spinel has a large solid solubility range at high temperatures. The present invention regulates the magnesium-aluminum ratio of the composite phase magnesium-aluminum spinel by adding magnesium oxide and aluminum oxide, rapidly hot-pressing and sintering the excess magnesium oxide and aluminum oxide to dissolve in the magnesium-aluminum spinel, and then heat-treating it as a nanophase precipitation strengthening material. Therefore, in some embodiments, the composite phase is composed of the following raw materials in parts by weight: 35-40wt% of magnesium oxide, 60-65wt% of aluminum oxide, and 0-5wt% of magnesium-aluminum spinel; in some embodiments, the composite phase is composed of the following raw materials in parts by weight: 50-55wt% of magnesium oxide, 45-50wt% of aluminum oxide, and 0-5wt% of magnesium-aluminum spinel; in some embodiments, the composite phase is composed of the following raw materials in parts by weight: 15-20wt% of magnesium oxide, 30-35wt% of aluminum oxide, and 65-70wt% of magnesium-aluminum spinel; to obtain a precipitation phase-reinforced hexagonal boron nitride composite ceramic material with better performance.
[0019] The present invention also provides a method for preparing a precipitate-reinforced hexagonal boron nitride composite ceramic material, comprising: mixing hexagonal boron nitride, magnesium oxide, aluminum oxide, and magnesium aluminum spinel to obtain a first product; Ball milling the first product and drying it to obtain a second product; The second product is sintered under vacuum conditions to obtain a third product: The third product is obtained by heat-treating the product under an inert atmosphere.
[0020] The sintering temperature affects the densification degree and mechanical properties of the ceramic material. Therefore, the present invention studies the sintering conditions. In some embodiments, the sintering conditions are to heat the temperature to 1600-1900°C and then keep the temperature for 5-60 minutes to obtain better density and mechanical properties.
[0021] Under the above-mentioned processing conditions, the present invention also optimizes the sintering temperature and time. In some embodiments, the sintering method is: heating to 1600-1700°C and keeping warm for 10-20 minutes to prepare high-performance hexagonal boron nitride composite ceramic materials at a lower temperature.
[0022] In some embodiments, the sintering method is: heating to 1650-1750° C. and keeping the temperature for 10-20 minutes; within this temperature range, high-performance hexagonal boron nitride composite ceramic materials can also be prepared.
[0023] The mechanical strength of the material increases first and then decreases with the increase of sintering temperature. Therefore, in some embodiments, the sintering method is: heating to 1700-1800°C and keeping warm for 10-20 minutes to obtain better mechanical properties at a higher temperature.
[0024] The temperature of heat treatment will affect the densification degree and mechanical properties of ceramic materials. Therefore, the present invention studies the conditions of heat treatment. In some embodiments, the heat treatment conditions are to heat the material to 1100-1300°C and then keep the temperature for 30-300 minutes to obtain better mechanical properties and density.
[0025] Under the above-mentioned treatment conditions, the present invention also optimizes the temperature and time of the heat treatment. In some embodiments, the heat treatment method is: heating to 1100-1200°C and keeping warm for 30-90 minutes; to prepare a high-performance hexagonal boron nitride composite ceramic material.
[0026] As the heat treatment time increases, the density and strength of the ceramic gradually increase. In some embodiments, the heat treatment method is: raising the temperature to 1100-1200°C and keeping it warm for 240-300 minutes, so as to further improve the performance of the hexagonal boron nitride composite ceramic material by extending the heat treatment time.
[0027] The mechanical strength of the material tends to first increase and then decrease with the increase of the heat treatment temperature. Therefore, in some embodiments, the heat treatment method is: heating to 1200-1300°C and keeping warm for 30-90 minutes to obtain better mechanical properties and density by increasing the heat treatment temperature.
[0028] High-performance hexagonal boron nitride composite ceramic materials can also be prepared by lower heat treatment temperatures and longer heat treatment times. Therefore, in some embodiments, the heat treatment method is: heating to 1100-1200°C and keeping warm for 240-300 minutes to improve the mechanical properties and density of the hexagonal boron nitride composite ceramic materials.
[0029] In summary, the present application provides a precipitate-reinforced hexagonal boron nitride composite ceramic material, wherein the raw materials of the composition include hexagonal boron nitride powder and a composite phase. The present application also provides a preparation method of the ceramic material, including raw material mixing, ball milling and drying, sintering, and heat treatment.
[0030] The present invention will be further described in detail below with reference to specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.
[0031] The following will be combined Figure 3 According to the precipitation phase strengthened hexagonal boron nitride composite ceramic material and its preparation method provided in this application, the precipitation phase strengthened hexagonal boron nitride composite ceramic material is produced.
[0032] Example 1 This embodiment is a specific example of preparing a precipitation phase strengthened hexagonal boron nitride composite ceramic product 1.
[0033] Step 1: Mix the raw materials Hexagonal boron nitride, magnesium oxide powder, aluminum oxide powder, and magnesium aluminum spinel powder are mixed in the following mass percentages to obtain a first product 1; Hexagonal boron nitride: 70%; magnesium oxide: 14.8%; aluminum oxide: 15.2%; magnesium aluminum spinel: 0%; Among them, the purity of hexagonal boron nitride powder is ≥99.0%, and the particle size is 1~2μm; the purity of magnesium oxide powder is ≥99.9%, and the particle size is 100~200nm; the purity of aluminum oxide powder is ≥99.9%, and the particle size is 250nm~750nm; the purity of magnesium aluminum spinel powder is ≥99.9%, and the particle size is 250nm~750nm.
[0034] Step 2: Ball mill drying The first product 1 was put into a ball mill and milled for 6 hours at a ball-to-material ratio of 3:1, anhydrous ethanol as the grinding medium, and a rotation speed of 300 r / min until the powder was fully mixed. It was then dried in an oven at 80°C for 12 hours to obtain the second product 1.
[0035] Step 3: Sintering The second product 1 is placed in a graphite mold and rapidly hot-pressed and sintered to obtain the third product 1.
[0036] The specific process conditions are as follows: The rapid hot pressing sintering method is: heating from 700°C to 1650°C at a heating rate of 50°C / min, keeping at this temperature for 10 minutes, and the vacuum degree is always kept less than or equal to 10Pa during the sintering process.
[0037] Step 4: Heat treatment The third product 1 is placed in a corundum crucible and heat-treated to obtain product 1.
[0038] The specific process conditions are as follows: Under nitrogen atmosphere, the temperature was raised from 50°C to 1300°C at a rate of 5°C / min and kept at this temperature for 60 min.
[0039] In this embodiment, after heat treatment, a hexagonal boron nitride composite ceramic material product 1 with precipitation phase reinforcement is obtained; after testing, the bending strength of the product 1 reaches 50.34 MPa. The microstructure of the product 1 is as follows Figure 2 As shown in (a) and (b), Figure 2 It can be concluded that the presence of a large number of nano-granular precipitates within the magnesia-alumina spinel phase within Product 1 exerts a strengthening effect. Compared to pure hexagonal boron nitride ceramics and hexagonal boron nitride composite ceramics sintered at the same temperature but without nano-precipitate reinforcement (Comparative Examples 1-3), Product 1 exhibits significantly improved flexural strength.
[0040] Example 2 This embodiment is a specific example of preparing a precipitation phase strengthened hexagonal boron nitride composite ceramic product 2.
[0041] Step 1: Mix the raw materials Hexagonal boron nitride, magnesium oxide powder, aluminum oxide powder, and magnesium aluminum spinel powder are mixed in the following mass percentages to obtain a first product 2; Hexagonal boron nitride: 70%; magnesium oxide: 14.8%; aluminum oxide: 15.2%; magnesium aluminum spinel: 0%; Among them, the purity of hexagonal boron nitride powder is ≥99.0%, and the particle size is 1~2μm; the purity of magnesium oxide powder is ≥99.9%, and the particle size is 100~200nm; the purity of aluminum oxide powder is ≥99.9%, and the particle size is 250nm~750nm; the purity of magnesium aluminum spinel powder is ≥99.9%, and the particle size is 250nm~750nm.
[0042] Step 2: Ball mill drying The first product 2 was placed in a ball mill and ball milled for 6 h at a ball-to-material ratio of 3:1, anhydrous ethanol as the grinding medium, and a speed of 300 r / min until the powder was fully mixed. It was then dried in an oven at 80°C for 12 h to obtain the second product 2.
[0043] Step 3: Sintering The second product 2 is placed in a graphite mold and rapidly hot-pressed and sintered to obtain the third product 2.
[0044] The specific process conditions are as follows: The rapid hot pressing sintering method is: heating from 700°C to 1650°C at a heating rate of 50°C / min, keeping at this temperature for 10 minutes, and the vacuum degree is always kept less than or equal to 10Pa during the sintering process.
[0045] Step 4: Heat treatment The third product 2 is placed in a corundum crucible and heat treated to obtain product 2.
[0046] The specific process conditions are as follows: Under a nitrogen atmosphere, the temperature was raised from 50°C to 1300°C at a rate of 5°C / min and held at this temperature for 300 minutes. In this embodiment, after heat treatment, a hexagonal boron nitride composite ceramic material product 2 with nano-reinforced phase precipitation was obtained. Testing showed that the flexural strength of product 2 reached 49.99 MPa.
[0047] The microstructure of product 2 is as follows Figure 2 As shown in (c) and (d), from Figure 2 It can be concluded that the presence of a large number of nano-granular second phases within the magnesia-alumina spinel phase within Product 2 provides a strengthening effect, but the size and content are slightly lower than those of Product 1. Compared with pure hexagonal boron nitride ceramics and hexagonal boron nitride composite ceramics sintered at the same temperature but without nano-precipitation reinforcement (Comparative Examples 1-3), Product 2 exhibits a significantly improved flexural strength.
[0048] Example 3 This embodiment is a specific example of preparing a precipitation phase strengthened hexagonal boron nitride composite ceramic product 3.
[0049] Step 1: Mix the raw materials Hexagonal boron nitride, magnesium oxide powder, aluminum oxide powder, and magnesium aluminum spinel powder are mixed in the following mass percentages to obtain a first product 3; Hexagonal boron nitride: 70%; magnesium oxide: 14.8%; aluminum oxide: 15.2%; magnesium aluminum spinel: 0%; Among them, the purity of hexagonal boron nitride powder is ≥99.0%, and the particle size is 1~2μm; the purity of magnesium oxide powder is ≥99.9%, and the particle size is 100~200nm; the purity of aluminum oxide powder is ≥99.9%, and the particle size is 250nm~750nm; the purity of magnesium aluminum spinel powder is ≥99.9%, and the particle size is 250nm~750nm.
[0050] Step 2: Ball mill drying The first product 3 was placed in a ball mill and milled for 6 h at a ball-to-material ratio of 3:1, anhydrous ethanol as the grinding medium, and a rotation speed of 300 r / min until the powder was fully mixed. It was then dried in an oven at 80°C for 12 h to obtain the second product 3.
[0051] Step 3: Sintering The second product 3 is placed in a graphite mold and rapidly hot-pressed and sintered to obtain the third product 3.
[0052] The specific process conditions are as follows: The rapid hot pressing sintering method is: heating from 700°C to 1750°C at a heating rate of 50°C / min, keeping at this temperature for 10 minutes, and the vacuum degree is always kept less than or equal to 10Pa during the sintering process.
[0053] Step 4: Heat treatment The third product 3 is placed in a corundum crucible and heat treated to obtain product 3.
[0054] The specific process conditions are as follows: Under a nitrogen atmosphere, the temperature was raised from 50°C to 1300°C at a rate of 5°C / min and maintained at this temperature for 60 minutes. In this example, after heat treatment, a hexagonal boron nitride composite ceramic material, Product 3, with nano-reinforced precipitation was obtained. Testing showed that Product 3 exhibited a flexural strength of 111.99 MPa. Compared to pure hexagonal boron nitride ceramics and hexagonal boron nitride composite ceramics sintered at the same temperature but without nano-reinforced precipitation (Comparative Examples 1-3), Product 3 exhibited significantly improved flexural strength.
[0055] Example 4 This embodiment is a specific example of preparing a precipitation phase strengthened hexagonal boron nitride composite ceramic product 4.
[0056] Step 1: Mix the raw materials Hexagonal boron nitride, magnesium oxide powder, aluminum oxide powder, and magnesium aluminum spinel powder are mixed in the following mass percentages to obtain a first product 4; Hexagonal boron nitride: 70%; Magnesium oxide: 14.8%; Aluminum oxide: 15.2%; Magnesium aluminum spinel: 0%; Among them, the purity of hexagonal boron nitride powder is ≥99.0%, and the particle size is 1~2μm; the purity of magnesium oxide powder is ≥99.9%, and the particle size is 100~200nm; the purity of aluminum oxide powder is ≥99.9%, and the particle size is 250nm~750nm; the purity of magnesium aluminum spinel powder is ≥99.9%, and the particle size is 250nm~750nm.
[0057] Step 2: Ball mill drying The first product 4 was put into a ball mill and milled for 6 hours at a ball-to-material ratio of 3:1, anhydrous ethanol as the grinding medium, and a rotation speed of 300 r / min until the powder was fully mixed. It was then dried in an oven at 80°C for 12 hours to obtain the second product 4.
[0058] Step 3: Sintering The second product 2 is placed in a graphite mold and rapidly hot-pressed and sintered to obtain the third product 4.
[0059] The specific process conditions are as follows: The rapid hot pressing sintering method is: heating from 700°C to 1750°C at a heating rate of 50°C / min, keeping at this temperature for 10 minutes, and the vacuum degree is always kept less than or equal to 10Pa during the sintering process.
[0060] Step 4: Heat treatment The third product 4 is placed in a corundum crucible and heat treated to obtain product 4.
[0061] The specific process conditions are as follows: Under a nitrogen atmosphere, the temperature was raised from 50°C to 1300°C at a rate of 5°C / min and held at this temperature for 300 minutes. In this example, after heat treatment, a hexagonal boron nitride composite ceramic material, Product 4, with nano-reinforced precipitation was obtained. Testing revealed that Product 4 exhibited a flexural strength of 101.28 MPa. Compared to pure hexagonal boron nitride ceramics and hexagonal boron nitride composite ceramics sintered at the same temperature but without nano-reinforced precipitation (Comparative Examples 1-3), Product 4 exhibited significantly improved flexural strength.
[0062] Example 5 This embodiment is a specific example of preparing a precipitation phase strengthened hexagonal boron nitride composite ceramic product 5.
[0063] Step 1: Mix the raw materials Hexagonal boron nitride, magnesium oxide powder, aluminum oxide powder, and magnesium aluminum spinel powder are mixed in the following mass percentages to obtain a first product 5; Hexagonal boron nitride: 70%; magnesium oxide: 9.8%; aluminum oxide: 20.2%; magnesium aluminum spinel: 0%; Among them, the purity of hexagonal boron nitride powder is ≥99.0%, and the particle size is 1~2μm; the purity of magnesium oxide powder is ≥99.9%, and the particle size is 100~200nm; the purity of aluminum oxide powder is ≥99.9%, and the particle size is 250nm~750nm; the purity of magnesium aluminum spinel powder is ≥99.9%, and the particle size is 250nm~750nm.
[0064] Step 2: Ball mill drying The first product 5 was placed in a ball mill and milled for 6 h at a ball-to-material ratio of 3:1, anhydrous ethanol as the grinding medium, and a rotation speed of 300 r / min until the powder was fully mixed. It was then dried in an oven at 80°C for 12 h to obtain the second product 5.
[0065] Step 3: Sintering The second product 5 is placed in a graphite mold and rapidly hot-pressed and sintered to obtain the third product 1.
[0066] The specific process conditions are as follows: The rapid hot pressing sintering method is: heating from 700°C to 1700°C at a heating rate of 50°C / min, keeping at this temperature for 10 minutes, and the vacuum degree is always kept less than or equal to 10Pa during the sintering process.
[0067] Step 4: Heat treatment The third product 5 is placed in a corundum crucible and heat-treated to obtain product 5.
[0068] The specific process conditions are as follows: Under a nitrogen atmosphere, the temperature was raised from 50°C to 1300°C at a rate of 5°C / min and maintained at this temperature for 60 minutes. In this example, the heat treatment yielded a hexagonal boron nitride composite ceramic material, Product 5, with nano-reinforced precipitation. Testing revealed that Product 5 exhibited a flexural strength of 56.90 MPa. Compared to pure hexagonal boron nitride ceramics and hexagonal boron nitride composite ceramics sintered at the same temperature but lacking nano-reinforced precipitation (Comparative Examples 1-3), Product 5 exhibited significantly improved flexural strength.
[0069] Example 6 This embodiment is a specific example of preparing a precipitation phase strengthened hexagonal boron nitride composite ceramic product 6.
[0070] Step 1: Mix the raw materials Hexagonal boron nitride, magnesium oxide powder, aluminum oxide powder, and magnesium aluminum spinel powder are mixed in the following mass percentages to obtain a first product 6; Hexagonal boron nitride: 70%; magnesium oxide: 9.8%; aluminum oxide: 20.2%; magnesium aluminum spinel: 0%; Among them, the purity of hexagonal boron nitride powder is ≥99.0%, and the particle size is 1~2μm; the purity of magnesium oxide powder is ≥99.9%, and the particle size is 100~200nm; the purity of aluminum oxide powder is ≥99.9%, and the particle size is 250nm~750nm; the purity of magnesium aluminum spinel powder is ≥99.9%, and the particle size is 250nm~750nm.
[0071] Step 2: Ball mill drying The first product 6 was put into a ball mill and milled for 6 hours at a ball-to-material ratio of 3:1, anhydrous ethanol as the grinding medium, and a rotation speed of 300 r / min until the powder was fully mixed. It was then dried in an oven at 80°C for 12 hours to obtain the second product 6.
[0072] Step 3: Sintering The second product 6 is placed in a graphite mold and rapidly hot-pressed and sintered to obtain the third product 6.
[0073] The specific process conditions are as follows: The rapid hot pressing sintering method is: heating from 700°C to 1700°C at a heating rate of 50°C / min, keeping at this temperature for 10 minutes, and the vacuum degree is always kept less than or equal to 10Pa during the sintering process.
[0074] Step 4: Heat treatment The third product 6 is placed in a corundum crucible and heat treated to obtain product 6.
[0075] The specific process conditions are as follows: Under a nitrogen atmosphere, the temperature was raised from 50°C to 1300°C at a rate of 5°C / min and maintained at this temperature for 300 minutes. In this example, after heat treatment, a hexagonal boron nitride composite ceramic material, Product 6, with nano-reinforced precipitation was obtained. Testing showed that Product 6 had a flexural strength of 57.90 MPa. Compared to pure hexagonal boron nitride ceramics and hexagonal boron nitride composite ceramics sintered at the same temperature but without nano-reinforced precipitation (Comparative Examples 1-3), Product 6 exhibited significantly improved flexural strength.
[0076] Example 7 This embodiment is a specific example of preparing a precipitation phase strengthened hexagonal boron nitride composite ceramic product 7.
[0077] Step 1: Mix the raw materials Hexagonal boron nitride, magnesium oxide powder, aluminum oxide powder, and magnesium aluminum spinel powder are mixed in the following mass percentages to obtain a first product 7; Hexagonal boron nitride: 70%; magnesium oxide: 9.8%; aluminum oxide: 20.2%; magnesium aluminum spinel: 0%; Among them, the purity of hexagonal boron nitride powder is ≥99.0%, and the particle size is 1~2μm; the purity of magnesium oxide powder is ≥99.9%, and the particle size is 100~200nm; the purity of aluminum oxide powder is ≥99.9%, and the particle size is 250nm~750nm; the purity of magnesium aluminum spinel powder is ≥99.9%, and the particle size is 250nm~750nm.
[0078] Step 2: Ball mill drying The first product 7 was put into a ball mill and milled for 6 h at a ball-to-material ratio of 3:1, anhydrous ethanol as the grinding medium, and a rotation speed of 300 r / min until the powder was fully mixed. It was then dried in an oven at 80°C for 12 h to obtain the second product 7.
[0079] Step 3: Sintering The second product 7 is placed in a graphite mold and rapidly hot-pressed and sintered to obtain the third product 7.
[0080] The specific process conditions are as follows: The rapid hot pressing sintering method is: heating from 700°C to 1750°C at a heating rate of 50°C / min, keeping at this temperature for 10 minutes, and the vacuum degree is always kept less than or equal to 10Pa during the sintering process.
[0081] Step 4: Heat treatment The third product 7 is placed in a corundum crucible and heat-treated to obtain product 7.
[0082] The specific process conditions are as follows: Under nitrogen atmosphere, the temperature was raised from 50°C to 1300°C at a rate of 5°C / min and maintained at this temperature for 60 minutes. In this embodiment, a composite ceramic material product 7 was obtained after heat treatment. After testing, the flexural strength of the product 7 reached 75.98 MPa.
[0083] The XRD pattern of product 7 is as follows Figure 1 As shown, it can be concluded that a solid-state reaction occurred between the hexagonal boron nitride and magnesia-aluminum spinel within Product 7, producing a boron mullite phase. The nano-precipitated phase could not be detected by XRD due to its size. Compared with pure hexagonal boron nitride ceramics and hexagonal boron nitride composite ceramics sintered at the same temperature but without nano-precipitated phase reinforcement (Comparative Examples 1-3), Product 7 has a significantly improved flexural strength.
[0084] Example 8 This embodiment is a specific example of preparing a precipitation phase strengthened hexagonal boron nitride composite ceramic product 8.
[0085] Step 1: Mix the raw materials Hexagonal boron nitride, magnesium oxide powder, aluminum oxide powder, and magnesium aluminum spinel powder are mixed in the following mass percentages to obtain a first product 8; Hexagonal boron nitride: 70%; magnesium oxide: 9.8%; aluminum oxide: 20.2%; magnesium aluminum spinel: 0%; Among them, the purity of hexagonal boron nitride powder is ≥99.0%, and the particle size is 1~2μm; the purity of magnesium oxide powder is ≥99.9%, and the particle size is 100~200nm; the purity of aluminum oxide powder is ≥99.9%, and the particle size is 250nm~750nm; the purity of magnesium aluminum spinel powder is ≥99.9%, and the particle size is 250nm~750nm.
[0086] Step 2: Ball mill drying The first product 8 was put into a ball mill and milled for 6 h at a ball-to-material ratio of 3:1, anhydrous ethanol as the grinding medium, and a rotation speed of 300 r / min until the powder was fully mixed. It was then dried in an oven at 80°C for 12 h to obtain the second product 8.
[0087] Step 3: Sintering The second product 8 is placed in a graphite mold and rapidly hot-pressed and sintered to obtain the third product 8.
[0088] The specific process conditions are as follows: The rapid hot pressing sintering method is: heating from 700°C to 1750°C at a heating rate of 50°C / min, keeping at this temperature for 10 minutes, and the vacuum degree is always kept less than or equal to 10Pa during the sintering process.
[0089] Step 4: Heat treatment The third product 8 is placed in a corundum crucible and heat-treated to obtain product 8.
[0090] The specific process conditions are as follows: Under a nitrogen atmosphere, the temperature was raised from 50°C to 1300°C at a rate of 5°C / min and maintained at this temperature for 300 minutes. In this embodiment, after heat treatment, a hexagonal boron nitride composite ceramic material product 8 with nano-reinforced phase precipitation was obtained. Testing showed that the flexural strength of product 8 reached 71.98 MPa.
[0091] The XRD pattern of product 8 is as follows Figure 1 As shown, it can be concluded that a solid-state reaction occurred between the hexagonal boron nitride and magnesia-aluminum spinel within Product 8, producing a boron mullite phase. The nanoprecipitates were not detectable by XRD due to their size. Compared to pure hexagonal boron nitride ceramics and hexagonal boron nitride composite ceramics (Comparative Examples 1-3) sintered at the same temperature but lacking nanoprecipitates, Product 8 exhibits significantly improved flexural strength.
[0092] Example 9 This embodiment is a specific example of preparing a precipitation phase strengthened hexagonal boron nitride composite ceramic product 9.
[0093] Step 1: Mix the raw materials Hexagonal boron nitride, magnesium oxide powder, aluminum oxide powder, and magnesium aluminum spinel powder are mixed in the following mass percentages to obtain a first product 9; Hexagonal boron nitride: 70%; magnesium oxide: 5.3%; aluminum oxide: 3.7%; magnesium aluminum spinel: 21%; Among them, the purity of hexagonal boron nitride powder is ≥99.0%, and the particle size is 1~2μm; the purity of magnesium oxide powder is ≥99.9%, and the particle size is 100~200nm; the purity of aluminum oxide powder is ≥99.9%, and the particle size is 250nm~750nm; the purity of magnesium aluminum spinel powder is ≥99.9%, and the particle size is 250nm~750nm.
[0094] Step 2: Ball mill drying The first product 9 was placed in a ball mill and milled for 6 h at a ball-to-material ratio of 3:1, anhydrous ethanol as the grinding medium, and a rotation speed of 300 r / min until the powder was fully mixed. It was then dried in an oven at 80°C for 12 h to obtain the second product 3.
[0095] Step 3: Sintering The second product 9 is placed in a graphite mold and rapidly hot-pressed and sintered to obtain the third product 9.
[0096] The specific process conditions are as follows: The rapid hot pressing sintering method is: heating from 700°C to 1700°C at a heating rate of 50°C / min, keeping at this temperature for 10 minutes, and the vacuum degree is always kept less than or equal to 10Pa during the sintering process.
[0097] Step 4: Heat treatment The third product 9 is placed in a corundum crucible and heat-treated to obtain product 9.
[0098] The specific process conditions are as follows: Under a nitrogen atmosphere, the temperature was raised from 50°C to 1300°C at a rate of 5°C / min and maintained at this temperature for 60 minutes. In this example, after heat treatment, a hexagonal boron nitride composite ceramic material product 9 with nano-reinforced precipitation was obtained. Testing showed that product 9 had a flexural strength of 67.73 MPa. Compared to pure hexagonal boron nitride ceramics and hexagonal boron nitride composite ceramics sintered at the same temperature but without nano-reinforced precipitation (Comparative Examples 1-3), product 9 exhibited significantly improved flexural strength.
[0099] Example 10 This embodiment is a specific example of preparing a precipitation phase strengthened hexagonal boron nitride composite ceramic product 10.
[0100] Step 1: Mix the raw materials Hexagonal boron nitride, magnesium oxide powder, aluminum oxide powder, and magnesium aluminum spinel powder are mixed in the following mass percentages to obtain a first product 10; Hexagonal boron nitride: 70%; magnesium oxide: 5.3%; aluminum oxide: 3.7%; magnesium aluminum spinel: 21%; Among them, the purity of hexagonal boron nitride powder is ≥99.0%, and the particle size is 1~2μm; the purity of magnesium oxide powder is ≥99.9%, and the particle size is 100~200nm; the purity of aluminum oxide powder is ≥99.9%, and the particle size is 250nm~750nm; the purity of magnesium aluminum spinel powder is ≥99.9%, and the particle size is 250nm~750nm.
[0101] Step 2: Ball mill drying The first product 10 was placed in a ball mill and milled for 6 h at a ball-to-material ratio of 3:1, anhydrous ethanol as the grinding medium, and a rotation speed of 300 r / min until the powder was fully mixed. It was then dried in an oven at 80°C for 12 h to obtain the second product 10.
[0102] Step 3: Sintering The second product 10 is placed in a graphite mold and rapidly hot-pressed and sintered to obtain a third product 10.
[0103] The specific process conditions are as follows: The rapid hot pressing sintering method is: heating from 700°C to 1700°C at a heating rate of 50°C / min, keeping at this temperature for 10 minutes, and the vacuum degree is always kept less than or equal to 10Pa during the sintering process.
[0104] Step 4: Heat treatment The third product 10 is placed in a corundum crucible and subjected to heat treatment to obtain product 10.
[0105] The specific process conditions are as follows: Under a nitrogen atmosphere, the temperature was raised from 50°C to 1300°C at a rate of 5°C / min and maintained at this temperature for 300 minutes. In this embodiment, after heat treatment, a hexagonal boron nitride composite ceramic material product 10 with nano-reinforced precipitation was obtained. Testing showed that the flexural strength of product 10 reached 62.90 MPa. Compared with pure hexagonal boron nitride ceramics and hexagonal boron nitride composite ceramics sintered at the same temperature but without nano-precipitation reinforcement (Comparative Examples 1-3), product 10 exhibited significantly improved flexural strength.
[0106] Comparative Example 1 This comparative example is a specific embodiment of preparing a reference product, in which the hexagonal boron nitride composite ceramic is not subjected to heat treatment. Step 1: Mix the raw materials Hexagonal boron nitride, magnesium oxide powder, aluminum oxide powder, and magnesium aluminum spinel powder are mixed according to the following mass percentages to obtain a first control material 1; Hexagonal boron nitride: 70%; magnesium oxide: 14.8%; aluminum oxide: 15.2%; magnesium aluminum spinel: 0%; Among them, the purity of hexagonal boron nitride powder is ≥99.0%, and the particle size is 1~2μm; the purity of magnesium oxide powder is ≥99.9%, and the particle size is 100~200nm; the purity of aluminum oxide powder is ≥99.9%, and the particle size is 250nm~750nm; the purity of magnesium aluminum spinel powder is ≥99.9%, and the particle size is 250nm~750nm.
[0107] Step 2: Ball mill drying The first control object 1 was placed in a ball mill and ball-milled for 6 h at a ball-to-material ratio of 3:1, anhydrous ethanol as the grinding medium, and a rotation speed of 300 r / min until the powder was fully mixed. The product was then dried in an oven at 80°C for 12 h to obtain the second control object 1.
[0108] Step 3: Sintering The second control object 1 was placed in a graphite mold and rapidly hot-pressed and sintered to obtain a control object 1.
[0109] The specific process conditions are as follows: The rapid hot pressing sintering method is: heating from 700°C to 1750°C at a heating rate of 50°C / min, keeping at this temperature for 10 minutes, and the vacuum degree is always kept less than or equal to 10Pa during the sintering process.
[0110] The control product obtained by vacuum sintering has an average bending strength of 76.95 MPa, which serves as comparative data for Examples 3 and 4.
[0111] Comparative Example 2 This comparative example is a specific embodiment of preparing a reference product. In the comparative example, the hexagonal boron nitride composite ceramic maintains the stoichiometric amount of the magnesium aluminum spinel and is not subjected to heat treatment. Step 1: Mix the raw materials Hexagonal boron nitride, magnesium oxide powder, aluminum oxide powder, and magnesium aluminum spinel powder are mixed according to the following mass percentages to obtain a first control material 2; Hexagonal boron nitride: 70%; magnesium oxide: 0%; aluminum oxide: 0%; magnesium aluminum spinel: 30%; Among them, the purity of hexagonal boron nitride powder is ≥99.0%, and the particle size is 1~2μm; the purity of magnesium oxide powder is ≥99.9%, and the particle size is 100~200nm; the purity of aluminum oxide powder is ≥99.9%, and the particle size is 250nm~750nm; the purity of magnesium aluminum spinel powder is ≥99.9%, and the particle size is 250nm~750nm.
[0112] Step 2: Ball mill drying The first control object 2 was placed in a ball mill and milled for 6 h at a ball-to-material ratio of 3:1, anhydrous ethanol as the grinding medium, and a rotation speed of 300 r / min until the powder was fully mixed. The product was then dried in an oven at 80°C for 12 h to obtain the second control object 2.
[0113] Step 3: Sintering The second control object 2 was placed in a graphite mold and rapidly hot-pressed and sintered to obtain a control object 2.
[0114] The specific process conditions are as follows: The rapid hot pressing sintering method is: heating from 700°C to 1750°C at a heating rate of 50°C / min, keeping at this temperature for 10 minutes, and the vacuum degree is always kept less than or equal to 10Pa during the sintering process.
[0115] The control product obtained by vacuum sintering has an average bending strength of 68.57 MPa, which serves as comparative data for Examples 3 and 4.
[0116] Comparative Example 3 This comparative example is a specific embodiment of preparing a reference product. In the comparative example, the hexagonal boron nitride composite ceramic is sintered using a traditional hot pressing sintering process without heat treatment.
[0117] Step 1: Mix the raw materials Hexagonal boron nitride, magnesium oxide powder, aluminum oxide powder, and magnesium aluminum spinel powder are mixed according to the following mass percentages to obtain a first control 3; Hexagonal boron nitride: 70%; magnesium oxide: 14.8%; aluminum oxide: 15.2%; magnesium aluminum spinel: 0%; Among them, the purity of hexagonal boron nitride powder is ≥99.0%, and the particle size is 1~2μm; the purity of magnesium oxide powder is ≥99.9%, and the particle size is 100~200nm; the purity of aluminum oxide powder is ≥99.9%, and the particle size is 250nm~750nm; the purity of magnesium aluminum spinel powder is ≥99.9%, and the particle size is 250nm~750nm.
[0118] Step 2: Ball mill drying The first control object 3 was placed in a ball mill and milled for 6 h at a ball-to-material ratio of 3:1, anhydrous ethanol as the grinding medium, and a rotation speed of 300 r / min until the powder was fully mixed. The product was then dried in an oven at 80°C for 12 h to obtain the second control object 3.
[0119] Step 3: Sintering The second control object 3 was placed in a graphite mold and hot-pressed and sintered to obtain a control object 3.
[0120] The specific process conditions are as follows: The hot pressing sintering method is: heating from 1000°C to 1750°C at a heating rate of 5°C / min, keeping at this temperature for 60 minutes, and the vacuum degree is always kept less than or equal to 10Pa during the sintering process.
[0121] The control product obtained by vacuum sintering has an average bending strength of 71.50 MPa, which serves as comparative data for Examples 3 and 4.
[0122] It can be concluded from the above technical solutions and embodiments that the precipitation phase reinforced hexagonal boron nitride composite ceramic material and preparation method thereof provided in this application have the following advantages: First, the precipitation phase reinforced hexagonal boron nitride composite ceramic material prepared by the technical solution provided in this application precipitates a nano-precipitate phase in the magnesium-aluminum spinel phase. The introduction of the nano-precipitate phase achieves a comprehensive improvement in the mechanical properties of the composite ceramic by pinning grain boundaries, hindering cracks, and inducing a toughening mechanism.
[0123] In the preparation method provided in the present application, during the raw material mixing stage and the heat treatment stage, a non-stoichiometric magnesium-aluminum spinel phase is obtained by regulating the ratio of the composite phase raw materials, and the excess magnesium and aluminum are precipitated in the spinel phase in the form of a nano-precipitate phase through heat treatment.
[0124] Furthermore, in order to verify the above analysis results, a sample composed of hexagonal boron nitride: 70%; magnesium oxide: 14.8%; aluminum oxide: 15.2%; magnesium aluminum spinel: 0% was vacuum sintered according to the sintering process parameters (holding at 1650℃ for 10 minutes) and heat treated according to the heat treatment process parameters (holding at 1300℃ for 1 hour in a nitrogen atmosphere). The surface morphology of the sample obtained by heat treatment was observed using a scanning electron microscope. Figure 2 As shown in the figure, the sample is mainly composed of two phases: hexagonal boron nitride (black) and magnesium aluminum spinel (white). A large number of granular reinforcement phases with a size of about 100 nm appear in the magnesium aluminum spinel phase, which improves its mechanical properties.
[0125] Second, the precipitation phase reinforced hexagonal boron nitride composite ceramic material prepared by the technical solution provided in this application produces boron mullite with unique physical and chemical properties and application potential in the field of thermal sealing. It can eliminate interface defects and reduce stress concentration, thereby improving its mechanical properties.
[0126] Furthermore, in order to verify the above analysis results, a sample with the composition of hexagonal boron nitride: 70%; magnesium oxide: 9.8%; aluminum oxide: 20.2%; and magnesium aluminum spinel: 0% was vacuum sintered according to the sintering process parameters (keeping at 1750°C for 10 minutes) and heat treated according to the heat treatment process parameters (1100°C).
[0127] X-ray diffraction (XRD) was used to detect the phase of the heat-treated sample, and its phase composition was as follows: Figure 1 As shown. Figure 1 and Figure 2 It can be concluded that after the preparation method provided in the present application, as the heat treatment time increases, the diffraction intensity of the magnesia-alumina spinel phase decreases and the diffraction intensity of the boron mullite phase increases.
[0128] Third, the precipitation phase reinforced hexagonal boron nitride composite ceramic material prepared by the technical solution provided in this application precipitates a nano-precipitate phase in the magnesium aluminum spinel phase, and its morphology and content can be controlled by changing the composition ratio, sintering temperature and heat treatment time to affect the overall performance of the composite ceramic.
[0129] In summary, the precipitation phase reinforced hexagonal boron nitride composite ceramic material provided by the present application, the raw materials of the composition include: hexagonal boron nitride powder and a composite phase. The present application also provides a preparation method of the above-mentioned ceramic material, including: raw material mixing, ball milling and drying, sintering and heat treatment. In the technical solution provided by the present application, a hexagonal boron nitride composite ceramic material with a reinforcing phase precipitated inside the composite phase and at the phase boundary between the composite phase and the hexagonal boron nitride matrix phase is prepared through the innovative design of raw materials and preparation methods; reinforcing phases with different contents and morphologies can also be obtained at the material phase boundary and in the composite phase through different sintering temperatures and heat treatment times; the comprehensive performance of the product is improved by improving interface bonding and precipitation phase strengthening; thereby effectively solving the technical defects in the prior art that the traditional hexagonal boron nitride ceramic materials have low hardness and strength, making it difficult to meet the performance requirements of harsh working conditions.
[0130] The foregoing description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art will readily appreciate that various modifications and variations of the present invention are possible. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention are intended to be within the scope of protection of the present invention.
Claims
1. A precipitation phase strengthened hexagonal boron nitride composite ceramic material, characterized in that: The raw materials include hexagonal boron nitride powder and a composite phase, wherein the composite phase is composed of the following raw materials in parts by weight: 0.01-52 wt% of magnesium oxide, 0-68 wt% of aluminum oxide, and 0-70 wt% of magnesium aluminum spinel.
2. The precipitation phase strengthened hexagonal boron nitride composite ceramic material according to claim 1, characterized in that: The mass of the composite phase is 10-50 wt % of the total mass of the ceramic material.
3. The precipitation phase strengthened hexagonal boron nitride composite ceramic material according to claim 1, characterized in that: The composite phase is composed of the following raw materials in parts by weight: 35-40 wt % of magnesium oxide, 60-65 wt % of aluminum oxide, and 0-5 wt % of magnesium aluminum spinel.
4. The precipitation phase strengthened hexagonal boron nitride composite ceramic material according to claim 1, characterized in that: The composite phase is composed of the following raw materials in parts by weight: 50-55 wt % of magnesium oxide, 45-50 wt % of aluminum oxide, and 0-5 wt % of magnesium aluminum spinel.
5. The precipitation phase strengthened hexagonal boron nitride composite ceramic material according to claim 1, characterized in that: The composite phase is composed of the following raw materials in parts by weight: 15-20 wt % of magnesium oxide, 30-35 wt % of aluminum oxide, and 65-70 wt % of magnesium aluminum spinel.
6. A method for preparing a precipitate-reinforced hexagonal boron nitride composite ceramic material, characterized in that: include: mixing hexagonal boron nitride, magnesium oxide, aluminum oxide, and magnesium aluminum spinel to obtain a first product; Ball milling the first product and drying it to obtain a second product; The second product is sintered under vacuum conditions to obtain a third product: The third product is obtained by heat-treating the product under an inert atmosphere.
7. The method for preparing the precipitation phase reinforced hexagonal boron nitride composite ceramic material according to claim 6, characterized in that: The sintering conditions are as follows: heating to 1600-1900° C. and then keeping the temperature for 5-60 minutes.
8. The method for preparing the precipitation phase reinforced hexagonal boron nitride composite ceramic material according to claim 6, wherein: The sintering method is: heating to 1600-1700° C. and keeping the temperature for 10-20 minutes; Alternatively, the sintering method is: heating to 1650-1750° C. and keeping the temperature for 10-20 minutes; Alternatively, the sintering method is: heating to 1700-1800° C. and keeping the temperature for 10-20 minutes.
9. The method for preparing the precipitation phase reinforced hexagonal boron nitride composite ceramic material according to claim 6, wherein: The heat treatment conditions are as follows: heating to 1100-1300° C. and then keeping the temperature for 30-300 minutes.
10. The method for preparing the precipitation phase reinforced hexagonal boron nitride composite ceramic material according to claim 6, characterized in that: The heat treatment method is: heating to 1100-1200°C and keeping the temperature for 30-90 minutes; Alternatively, the heat treatment method is: heating to 1100-1200° C. and keeping the temperature for 240-300 minutes; Alternatively, the heat treatment method is: heating to 1200-1300° C. and keeping the temperature for 30-90 minutes; Alternatively, the heat treatment method is: heating to 1100-1200° C. and keeping the temperature for 240-300 minutes.